Perceptions on Academic Rhinologist Compensation Models: An ARS Survey - Kiran Abraham‐Aggarwal; Xiaoxuan Chen; Daniel J. Spertus; Shriya Suresh; Andrew B. Yang; Ashutosh Kacker (OTO Open, 2025)
Abstract Objective To evaluate the perceptions of American Rhinologic Society (ARS) members on the compensation models of academic rhinologists and their impact on clinical practice, teaching, and academic responsibilities. Study Design Survey study. Setting Academic rhinologists across the United States who are members of the ARS. Methods A twenty‐six‐question survey was distributed to 295 ARS members. The survey collected demographic information such as years of experience, geographic location, practice setting, and consultation volume. It also explored various compensation models and their impact on compensation, patient volume, case types, and the ability to support teaching and academic responsibilities. Results Out of 295 surveyed ARS members, 107 responded (36%), and 80 academic rhinologists were included in the final sample. Respondents varied in experience and geographic distribution. Most respondents were salaried (69%), while 63% were under relative value units (RVU)‐based models, and 25% were under collections‐based models. Additionally, 66% reported poor or no support for research and educational activities. Compensation models were found to influence patient volume (28%), procedure choices (14%), and academic duties, with 55% of respondents indicating reduced engagement with students. Conclusion Although a plurality of respondents (39%) believed that salaried models are most conducive to balancing academic and clinical responsibilities, survey findings highlight a dissonance. Respondents under collections‐based models were more likely to feel adequately supported (64.71%) compared to those under salaried or RVU‐based models. This suggests that although many perceive salaried models as ideal for balance, collections‐based models may better address financial and structural needs, emphasizing the importance of developing flexible, tailored compensation structures that align with individual and institutional goals while fostering academic productivity.